The user structure in Brazil's tropical rain forest - Peter Herman May; Eustáquio J. Reis (Kiel Institute of World Economics (IfW); ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 1993)
This paper presents quantitative evidence on the relationship between forest conversion and the productivity of agropastoral activities in the Legal Amazon. The extraction of timber products such as wood, fuelwood and charcoal is related to the process of agropastoral expansion in this region with the aim of providing physical coefficients to define intersectoral connections in Brazil's economy. The paper is organized as follows. Section I makes a geographical characterization of the original vegetation types of the region according to its principal geopolitical subdivisions. Section II presents evidence on deforestation rates and gross areas affected. Section III describes the principal sources of deforestation. Section IV describes sectoral activities and land occupation patterns distinguishing between forested and non-forested areas. Section V analyses major determinants of productivity in agropastoral activities following this broad vegetation distinction. Section VI provides gross estimates of wood removal associated with agropastoral expansion, and compares this with wood and fuel production figures. Conclusions are presented in Section VII.
Keywords: 330; Landwirtschaftliche Bodennutzung; Abholzung; Forstwirtschaft; Brasilien; Amazonasgebiet; Tropen; Landwirtschaft